Sustainable masonry : stability and behavior of structures - Ciblac, Thierry; Morel, Jean-Claude; Wiley eBooks (London : ISTE, 2014)
This book is the result of the meeting of two complementary approaches to the same subject: masonry. The first is the approach developed by Thierry Ciblac at the Ecole Nationale Supérieure d'Architecture de Paris la Villette (National School of Architecture of Paris La Villette, France), which revisits historical design methods using digital tools. The second consists of studies led by Jean-Claude Morel at the Ecole Nationale des Travaux Publics de l'Etat (National School of Civil Engineering, Lyon, France), which are based on experiments with masonry structures of earth materials. The convergence of these two approaches occurs through the common use of the theory of yield design. This book covers the impact of sustainable masonry on the environment, touting the many benefits of utilizing local and/or low embodied energy materials in the construction of sustainable buildings. Introducing readers to and promotes understanding of the mechanical stability of masonry structures in a contemporary context. This approach will allow contractors to carry out diagnostics on existing heritage and to design new structures. Book jacket.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Masonry; Structural stability; TECHNOLOGY & ENGINEERING -- Construction -- General; Masonry; Structural stability; Electronic books